Reaffirmation of agricultural policy in the work of Dragoljub Jovanović - a look into the past, a review of the present, and a foundation for the future - Tmušić, Marko (Sociološki pregled, 2022)
The problem of agriculture was one of the central issues in the scientific and, later, in the political activities of Dragoljub Jovanović. His understanding of the importance of agriculture, as well as diagnosing the problems that the village, as a territorial unit of agriculture, and the peasant, as a basic economic entity, face in agriculture, is an important basis for analyzing both past and present problems of Serbian agriculture. The answer to the dilemma about Serbian agriculture as its development opportunity, or as a kind of myth that has lasted for more than a century, can be found in Jovanović’s most important conclusions. In this paper, we will present his concept of agricultural policy by analyzing two key categories: the village (and the peasant) and cooperatives. Relying on the established conclusions, we will offer some useful guidelines for the future development of agriculture in Serbia.
Keywords: Dragoljub Jovanović; agricultural policy; village and peasant; cooperatives; agriculture in Serbia